The Effect of Role-Play Learning Strategy and Self-Concept on Social Skills of Children Age 5-6 Years Old in Aisyah Az-Zahra Medan - Syamsu Nahar; Wahyuddin Nur Nasution; Sunita Sari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This study aims to determine: (1) differences in the social skills of children who carry out learning activities using macro role playing strategies and those using micro role playing, (2) differences in social skills of children who have high self-concept and children who have low self-concept, and (3) the interaction between role playing strategies and self-concept on social skills. The populations in this study were children aged 5-6 years. This research was conducted at PAUD Aisyah Az-zahra Medan. The research method used was quasi-experimental. The collection technique was a questionnaire and a test, then the data analysis technique was a two-way analysis of variance. The results showed (1). the average social skills of children who learn to use macro role playing strategies are higher, namely = 8.80 compared to those who use micro role playing strategies = 6.50, with f-count = 9.096 > f-table = 3.48, with a level significant 0.05, (2) the average social skills of children who have high self-concept is higher with an average = 9.15 while the average social skills of children who have low self-concept = 7.96 with f-count = 5,967> f-table = 3.48 with a significant level of 0.05, and (3) there is an interaction between playing with self-concept on children's social skills with f-count = 4.591> f-table = 3.48 at a significant level of 0, 05.